Comparative study of indices related to floods in morphometric river basin of high Jacuí And Vacacaí -Vacacaí MIRIM –RS - Georgin, Jordana; Oliveira, Gislayne Alves; Rosa, Ana Lúcia Denardin da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Knowledge of morphometric characteristics of a watershed is essential to the development of plans aimed at understanding the processes in this medium. The aim of this study was to analyze and compare the morphometric characterization of the river basins of the High Jacuí and Vacacaí, in Rio Grande do Sul State and relate to possible flooding occurrences. For this, from data SRTM images and shapefiles the river basins of the land morphometric parameters were calculated for the study of the hydrological behavior of the basin. The watershed of the Upper Jacuí and Vacacaí have elongated profile, compactness coefficient of 1.4 and 1:36, form factor of 0.3547 and 0.4344 and circularity index of 0.4977 and 0.5312, respectively, indicating that they are unlikely to flooding. The maximum altitude was found to be 773 m and 4 m minimum relief of the terrain showed lower slopes above 4%. The more elongated shape of the basin indicates that precipitation over it focuses on different points, contributing to minimize the influence of the intensity of rainfall, which could cause major changes in the flow of the stream.